Analysis Implementation of Online Auction (E-Auction) at the State Assets and Auction Service Office (KPKNL) Jakarta - Andriana, Nina; Giovanni, Rama; Akhmad Priharjanto (IJESS International Journal of Education and Social Science, 2023)
This research aims to analyze the implementation of e-auctions, the obstacles that occur, and efforts to overcome obstacles at the State Assets and Auction Service Office (KPKNL) Jakarta. The method used by the author is a qualitative method, with research specifications being analytical descriptive. The data analysis method used is descriptive qualitative. The research was carried out at KPKNL Jakarta. Qualitative research method with data acquisition techniques through surveys and in-depth interviews using purposive sampling techniques. The results of the research state that the public's understanding of the implementation of e-auction auctions is less than their understanding of the implementation of conventional auctions. Public understanding regarding auction administration is also still very limited. Besides that, there are still many people who think that holding auctions is State Tax Revenue, not Non-Tax State Revenue (PNBP). Even though in implementing the e-auction at KPKNL Jakarta there are still several obstacles originating from external factors, KPKNL Jakarta continues to make efforts to overcome these obstacles to optimize the implementation of e-auctions at KPKNL Jakarta.